Quercetin attenuates cisplatin-induced fatigue through mechanisms associated with the regulation of the HPA axis and MCP-1 signaling - Chuang, Cheng-Hung; Tai, Yu-An; Wu, Ting-Jing; Ho, Ying-Jui; Yeh, Shu-Lan (Frontiers in Nutrition, 2025)
IntroductionCancer-related fatigue (CRF) is a common symptom induced by chemotherapy. The main objective of the present study was to investigate whether quercetin regulates the hypothalamic-pituitary-adrenal (HPA) axis and chemoattractant protein-1 (MCP-1) signaling, two factors contributing to CRF in mice exposed to cisplatin.MethodsMale BALB/c mice were randomly assigned to the following five groups for 15 weeks: Control, CDDP, CDDP+TAK779 (an antagonist of MCP-1 receptor, human CC chemokine receptor R2 (CCR2)), CDDP+OQ (a diet containing 1% quercetin) and CDDP+IQ (quercetin given by ip, 10 mg/kg, 3 times/week).ResultsThe results first showed that OQ and IQ significantly increased grip strength and locomotor activity, decreased plasma cortisol/corticosterone levels, and decreased the corticotropin releasing hormone (CRH) mRNA level in the brain tissues in mice exposed to CDDP. OQ and IQ also decreased CDDP-induced plasma levels of MCP-1 as well as the mRNA expression of MCP-1 and CCR2 in the brain stem. TAK779 significantly increased grip strength and tended to decrease the cortisol/corticosterone levels in CDDP-exposed mice, indicating the association between the HPA axis and MCP-1 signaling.ConclusionTaken together, the study suggests that quercetin could attenuate CDDP-induced CRF through the mechanisms associated with downregulation of the HPA axis and MCP-1 signaling in mice.